Run Zan run - MacPhail, Catherine 1946-2021 (Bloomsbury, 2011)
"When Zan steps out of her cardboard box and into Katie's life, lonely Katie Cassidy becomes a school hero. And it's all thanks to Zan! But who is Zan and why is she so desperate to keep out of the spotlight? Soon Katie finds out that if Zan's identity is revealed, she will be in terrible danger. How can Katie help her new best friend?" Klappentext
Keywords: Bullying in school / Fiction; Homeless girls / Fiction; Schikane; Abenteuer; Obdachlosigkeit; Freundschaft; Mädchen; Detektiv; Ausreißerin; Hilfeleistung; Rätsel; Kind; Fiktionale Darstellung; Kinderbuch